Efficient Alignment of Illumina‐Like High‐Throughput Sequencing Reads with the GEnomic Multi‐tool (GEM) Mapper. Issue 1 (19th June 2015) - Marco‐Sola, Santiago; Ribeca, Paolo
Abstract: Modern Illumina‐like high‐throughput sequencing machines allow the cheap decoding of great amounts of DNA. The GEnomic Multi‐tool (GEM) mapper is one of the fastest and most sensitive methods known to date to align such data to a known genomic reference. This unit explains how to use it effectively. © 2015 by John Wiley & Sons, Inc.